FARMER EMPOWERMENT FOR SUPPLYING CROTALARIA JUNCEA AS A SOURCE OF ORGANIC FERTILIZER AT DRY LAND - lolita endang susilowati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
The community extension service aim to upgrade farmers' knowledge about organic fertilizer; (2) introduce the Crotalaria juncea cultivation as a source of organic fertilizer in situ; (3) demonstrate the potential of Crotalaria juncea as an organic fertilizer for crops on dry land. This activity was conducted at village of Sukadana and Gumantar, Regency of North Lombok for eight months. The method used was participatory approach with stages of the activity as follows: (1) socialization of the activity plan to the cooperator farmers; (2) extension services to farmers in respect of organic matter role in increasing soil fertility; (3) demonstrate to farmers about the Crotalaria cultivation and its utilization as organic fertilizer by making experimental plots; (4) evaluation of the achievement of the activity objectives. Results of the activity shown that (1) farmers' knowledge about organic fertilizer and its role for soil fertility increased; (2) farmers interested to cultivate Crotalaria juncea to be used as a source of organic fertilizer at dry land; (3) farmers responded positively to this program and confirmed that it provides economic benefits in agriculture